PENDIDIKAN TERHADAP HUBUNGAN KEPRIBADIAN DAN MOTIF DENGAN PERILAKU KEWARGANEGARAAN ORGANISASIONAL PADA INDUSTRI PERBANKAN DI INDONESIA - D. Wahyu Ariani (Jurnal Keuangan dan Perbankan, 2010)
The goal of this research was to test education factor as the moderate variable ofthe relationship model among core self-evaluation personality, motives, and organizationalcitizenship behavior. The research integrated the use of attribution theory, social exchangetheory, core self- evaluation theory. A survey was conducted by using questionnaires fromprevious research. The questionnaires were sent to 128 branches of the bank industry locatedin 16 major cities in Java. The samples consisted of 636 tellers. Validity tests and reliabilitytests were used to test the questionnaires contents. The Structural Equation Modelling (SEM)was used to test the relationship among the variables. The result proved that educationmoderated the relational model between core self- evaluation personality, organizationalconcern motives, pro-social values motives, impression management motives and organiza-tional citizenship behavior.